m6A Reader PRRC2A Promotes Colorectal Cancer Progression via CK1ε‐Mediated Activation of WNT and YAP Signaling Pathways - Xi Wu; Shiyang Wang; Yuwei Pan; Mengzhen Li; Manyu Song; Hanfu Zhang; Min Deng; Xu Yang; Jiuzhi Xu; Shuo Zhang; Jinhua Zhang; Fengchao Wang; et al. (Advanced Science)
Abstract Colorectal cancer (CRC) is the third most common cancer type and the second highest mortality rate among cancers. However, the mechanisms underlying CRC progression remain to be fully understood. In this work, a recently identified m6A‐modified RNA reader protein Proline‐rich Coiled‐coil 2a (PRRC2A) is markedly upregulated in CRC, and intestinal epithelium‐specific deletion of Prrc2a significantly suppressed tumor cell growth, stemness, and migratory capacity, while its overexpression promoted these behaviors. Through multiomics analysis, PRRC2A directly targeted CSNK1E (encoding CK1ε), maintaining its RNA stability in an m6A‐dependent manner, and that elevated CK1ε can concomitantly result in activation of the WNT and YAP signaling pathways. Interestingly, PRRC2A is directly regulated by the transcription factor ATF1 in its promoter. In summary, the work reveals a novel mechanism by which m6A reader PRRC2A promotes colorectal cancer progression via CK1ε and aberrant upregulation of WNT and YAP signaling. Therefore, PRRC2A and CK1ε can be potential therapeutic targets for treating CRC.